2004
DOI: 10.1158/1078-0432.ccr-03-0110
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic Characteristics of a Germ-Line KIT Mutation in a Large Kindred with Gastrointestinal Stromal Tumors, Hyperpigmentation, and Dysphagia

Abstract: Purpose: Somatic mutations that result in the activation of the growth factor receptor KIT are commonly found in gastrointestinal stromal tumors (GISTs). Six families have been reported in which a germ-line mutation in KIT is associated with an autosomal dominant predisposition to the development of GISTs. Hyperpigmentation, urticaria pigmentosa, and dysphagia have been described in some, but not all, families. Preliminary correlations between the site of mutation and the clinical phenotype have been proposed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
79
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(85 citation statements)
references
References 21 publications
4
79
2
Order By: Relevance
“…For instance, the median age at diagnosis has been described in one study to decrease in successive generations possibly because of better diagnostic imaging or evolving genetic stability. 12 This observation has not been reported in other studies and has not been confirmed in another large kindred. Additionally, histopathologic evaluation of GISTs resected from kindreds has not been evaluated in terms of the consensus criteria for risk stratifications of GIST using mitotic rates and tumor size.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…For instance, the median age at diagnosis has been described in one study to decrease in successive generations possibly because of better diagnostic imaging or evolving genetic stability. 12 This observation has not been reported in other studies and has not been confirmed in another large kindred. Additionally, histopathologic evaluation of GISTs resected from kindreds has not been evaluated in terms of the consensus criteria for risk stratifications of GIST using mitotic rates and tumor size.…”
mentioning
confidence: 62%
“…In contrast to sporadic gastrointestinal tumors that present with a single primary tumor, surgical intervention performed on an individual with a hereditary GIST may reveal tens to hundreds of tumor nodules. 3,5,7,[9][10][11][12][30][31][32] The mitotic rate of the tumors in most of these families (those who were documented) appear to be low suggesting that these tumors appear indolent compared with sporadic GIST. 3,9,10,12,13,30,33 Interestingly, 2 patients in our study presented with metastases at diagnosis despite displaying variable mitotic rates (1 with 5 mitoses per 50 hpf and 1 with 30 mitoses per 50 hpf.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations